Designing a Mobile Chatbot For Elementary School Vocabulary - Yohandi, KG; Sani, MI (International Journal of Computer Sciences and Engineering, 2020)
English is one of the languages used throughout the world and has also been established as an international language. So the interest in learning English must start early. Children who are raised in elementary school must have been introduced to English. This paper aims to develop an educational-based chatbot and provide an evaluation of its use as a medium for learning English vocabulary for grade elementary school children using the Machine Learning method. With the dataset is the vocabulary obtained from a second grade elementary school book. The results showed that the development of chatbots could motivate elementary school children to learn English vocabulary more often.